2018
DOI: 10.1017/s0022215118001172
|View full text |Cite
|
Sign up to set email alerts
|

The importance of petrous apex and peri-carotid pneumatisation in subtotal petrosectomy and blind sac closure: a radiological study

Abstract: The degree of separation of middle-ear air cells from the Eustachian tube or nasopharynx, and the relevant anatomy, are reviewed. This knowledge helps to optimise the outcome of subtotal petrosectomy and blind sac closure. The frequency and process of pneumatisation of the petrous apex, and its connections with the middle ear, have been radiologically confirmed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 10 publications
0
8
1
Order By: Relevance
“…A previous study of 29 paediatric CT scans found evidence of pneumatisation occurring in a child as young as five years. 22 In our study, the youngest child with evidence of petrous apex pneumatisation was a one-year-old female, with 1 per cent of her petrous apices being pneumatised. The extent of pneumatisation was also found to vary with age in a study of 299 CT scans, with younger age being associated with greater pneumatisation; however, that study did not focus on children, with the median age of patients being 50 years (interquartile range, 33-63 years).…”
Section: Agementioning
confidence: 52%
See 3 more Smart Citations
“…A previous study of 29 paediatric CT scans found evidence of pneumatisation occurring in a child as young as five years. 22 In our study, the youngest child with evidence of petrous apex pneumatisation was a one-year-old female, with 1 per cent of her petrous apices being pneumatised. The extent of pneumatisation was also found to vary with age in a study of 299 CT scans, with younger age being associated with greater pneumatisation; however, that study did not focus on children, with the median age of patients being 50 years (interquartile range, 33-63 years).…”
Section: Agementioning
confidence: 52%
“…For example, when performing a subtotal petrosectomy with blind sac closure, the degree of petrous apex pneumatisation affects the extent of temporal bone resection. 22 Limitations High-resolution CT scanning is not typically used for neuroimaging in children in New Zealand because of radiation exposure, unless clinically indicated, often as a result of temporal bone or otological disease. The 4 mm thickness between slices meant an assumption had to be made that there was no variability in air cell area between slices that might affect the accuracy of the volume calculations.…”
Section: Clinical Relevancementioning
confidence: 99%
See 2 more Smart Citations
“…24 However, since in 96% of temporal bones the carotid artery forms a barrier between the air spaces anterior and posterior, particular attention to the carotid artery is warranted to achieve successful ET occlusion. 25 Ugo Fisch, the name giver of "subtotal petrosectomy," recommended that the internal carotid artery should be followed with diamond burr in order to remove the bony ET as far as the isthmus. 26 After the mucosa is coagulated the obliteration should be done "with bone wax, which is firmly packed with a suction tip covered with a neurosurgical cottonoid."…”
Section: Discussionmentioning
confidence: 99%